Sosialisasi Pencegahan Dan Penanganan Kasus Bullying Pada Siswa Sekolah Dasar - Amhar Maulana Harahap; Muhammad Amsal Nasution; Khoirun Nisa Zein Lubis; Enni Kholidah Daulay; Kholidah Hannum; Hoiriah Siregar; Rahma Mardiani Lubis; Lanniari Hasibuan; Doarni Lubis; Nisma Sari Nasution; Muhammad Rinaldi Harahap (Getpress Management Journals, 2025)
This study aims to analyze the phenomenon of bullying in rural elementary schools and to develop prevention strategies through a participatory approach in Paranbatu Village. The research employs a descriptive qualitative method, utilizing interviews, observations, and documentation involving teachers, students, and parents. The findings indicate that bullying cases in rural elementary schools still frequently occur in the form of teasing, exclusion, and minor physical violence, which are often perceived as normal by the community. The lack of awareness and limited teacher training are identified as the main factors behind the ineffective handling of such cases. Through socialization activities involving teachers, students, and parents, there has been a noticeable improvement in understanding, concern, and collaboration in preventing and addressing bullying. This participatory approach has proven effective in creating a safe and conducive learning environment while strengthening the relationship between schools and families in fostering an anti-bullying culture within rural communities.